KEWENANGAN KEPOLISIAN DAERAH BALI DALAM PENANGANAN KASUS TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH WARGA NEGARA ASING (WNA) TERHADAP WARGA LOKAL YANG VIRAL MELALUI MEDIA SOSIAL - Salu, Chintia Bongga; Susrama, I Nengah (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
The authority of the police in handling cases of criminal acts of persecution committed by foreign nationals that go viral through social media is often a public discussion. The problem in this case is how the authority of the police in handling cases of criminal acts of persecution committed by foreign nationals that went viral on social media and the inhibiting factors in handling the case. This research was carried out in the jurisdiction of the South Kuta Police Chief. The type of research used is empirical law using legal system theory, law enforcement theory and authority theory. From the results of the research conducted in this case, the police often wait for complaints or reports first, because there are no reports or complaints that the perpetrators flee or hide, there is a lack of evidence obtained by the police. The police already have an online service to receive complaints from the public, making it easier for people to use their personal social media to participate in law enforcement in Indonesia.